2008
DOI: 10.1007/s11881-008-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of context in the word recognition process by adults with a significant history of reading difficulties

Abstract: We examined whether university students who report a significant history of reading difficulties (RD; n = 24) differed from university students with no history of reading difficulties (NRD; n = 31) in how sentence context affects word recognition. Experiment 1 found no differences in how congruent sentence primes or syntactic manipulations of the sentence primes affected the performance of the two groups. However, only the RD group displayed a significant inhibition effect when the target word was preceded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
3
8
0
1
Order By: Relevance
“…On timed testing, these studies found significant differences in reading comprehension in favor of readers without disabilities. However, no significant differences between readers with and without LD were found when comprehension was scored as the number of items correct out of the items actually attempted in the time permitted, rather than the number of correct answers out of all of the items presented (Corkett & Parrila, 2007;Deacon, Parrila, & Kirby, 2006).…”
Section: Phonological Awareness and Reading Mechanicsmentioning
confidence: 82%
“…On timed testing, these studies found significant differences in reading comprehension in favor of readers without disabilities. However, no significant differences between readers with and without LD were found when comprehension was scored as the number of items correct out of the items actually attempted in the time permitted, rather than the number of correct answers out of all of the items presented (Corkett & Parrila, 2007;Deacon, Parrila, & Kirby, 2006).…”
Section: Phonological Awareness and Reading Mechanicsmentioning
confidence: 82%
“…Así, los autoinformes han formado parte del procedimiento habitual destinado a establecer el criterio de selección de la muestra y establecimiento de grupos (Bekebrede, Van der Leij, Plakas, Shareb y Morfidi, 2010;Birch y Chase, 2004;Corkett y Parrila, 2008;Hatcher et al, 2002;Ramus et al, 2003;Scarborough, 1991; y en el nutrido grupo de publicaciones de Finlandia Torppa, Eklund, van Bergen, y Lyytinen, 2011, entre otros).…”
Section: Introductionunclassified
“…It may follow that the largest achievement gaps for students with a self-reported history of reading difficulties will be in isolated word reading, with lower levels of impairment in reading comprehension. The semantic and syntactic contexts provided by connected text may facilitate comprehension for students with a self-reported history of reading difficulties (see Corkett & Parrila, 2008). Alternatively, if processes specific to reading fluency or comprehension are impaired for students with a self-reported history of reading difficulties, text-reading measures may be at least as impaired as isolated word reading.…”
mentioning
confidence: 99%